Interplay of Christian Missions, Batak Traditions, and Colonial Influence in North Tapanuli, Indonesia in 1861-1940 - JLM Siahaan; Yety Rochwulaningsih; Singgih Tri Sulistiyono; Ichwan Azhari (Indonesian Historical Studies, 2025)
This study focuses on the missionary movement of the Rhein Missionary Society (RMG) and its impact on the political and social dynamics of the Batak people. The RMG missionary movement, which began in the 19th century, became one of the key drivers in the spread of Christianity in the Toba Batak region. Additionally, the involvement of the missionary movement alongside the Dutch colonial government brought significant changes to the social life of the Batak people. Therefore, this article highlights the local social and political changes triggered by the Padri attacks, which also influenced the community's acceptance of Christianity. The historical method is used in this article to reveal various responses to Christian missions, ranging from traditional acceptance to integration into Christian traditions. This study also analyses how Dutch colonialism influenced the spread of Christianity, as well as the social, political, and cultural transformations that occurred. These findings offer a new perspective on the interaction between Christian missions, Batak customs, and colonialism in shaping the history of religion in the Batak region.